Tailored silane based sorbent coatings for compact atmospheric water harvesting devices - Ortiz, Nathan; Rao, Sameer (Frontiers in Water, 2025)
Sorbent coatings posses quick sorption kinetics due to their thin characteristic length scales for mass transfer and serve as an effective way to host sorbent material in a compact footprint. A tailorable coating technique is developed in this work to optimize the cycling ability of sorption based atmospheric water harvesters. Silane is used as a binding agent to adhere zeolite powder (AQSOA Z02) to thin aluminum sheets to provide a structurally sound and volumetrically dense method of packaging the sorbent while maintaining extremely fast sorption kinetics. A novel coating layering technique was used to manipulate the coating thickness slowing the adsorption times in exchange for better coating weight (kgsorbent(m2)-1). Through the multi coating technique we achieved a sorbent coating capable of collecting 1.167 kgwater(m2)-1 and when projected onto a finned heat exchanger 458 kgwater(m3)AHX-1day-1. These are highly competitive numbers especially when considering the relatively low sorbent uptake of AQSOA Z02 (32% at RH>30% and T=25°C) when compared to modern sorbents such as Ni2Cl2(BTDD) that has uptake of 80% (RH>30% and T=25°C). We outline the coating, characterization and system projection calculations which can be extrapolated in the future to modern materials and alternative form factors.